2019
DOI: 10.36740/wlek201904121
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia as Risk Factor of Atherosclerosis in Patients With Chronic Obstructive Pulmonary Disease

Abstract: Introduction: Atherosclerosis is one of the most common co-morbidities observed in chronic obstructive pulmonary disease. A better understanding of mechanisms of atherosclerosis in patients with chronic obstructive pulmonary disease is needed to improve clinical outcomes. The aim: to evaluate the plasma levels of lipid parameters, atherogenic indices, systemic inflammatory markers and to assess their relationship with the severity of chronic obstructive pulmonary disease. Materials and methods: A total of 72 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Data presented as mean ± standard deviation (n = 6). *p < .05, **p < .01 compared with the control; # p < .05, ## p < .01 compared with cholesterol treatment group Dyslipidemia is a key risk factor for AS and is also the main pathological manifestation (Ternushchak & Tovt-Korshynska, 2019). Studies have shown that it is an effective way to prevent and treat AS by regulating blood lipid levels; currently, statins are the main therapeutic drugs for the treatment of AS because of its hypolipidemic effect (Kouhpeikar et al, 2020;Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Data presented as mean ± standard deviation (n = 6). *p < .05, **p < .01 compared with the control; # p < .05, ## p < .01 compared with cholesterol treatment group Dyslipidemia is a key risk factor for AS and is also the main pathological manifestation (Ternushchak & Tovt-Korshynska, 2019). Studies have shown that it is an effective way to prevent and treat AS by regulating blood lipid levels; currently, statins are the main therapeutic drugs for the treatment of AS because of its hypolipidemic effect (Kouhpeikar et al, 2020;Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Arterial stiffness is a commonly used index for clinical prediction of carotid artery disease, which is a non-invasive examination. It was found that age, dyslipidemia, course of disease, V-type involvement and high mean arterial pressure were independent risk factors for increased arterial stiffness in patients with COPD [15,16] . In this study, the level of RI and PI of the patients with COPD in the observation group were lower than those in the control group (P < 0.05); the IMT, total plaque area, and number of plaques in the observation group were higher than those in the control group ( P < 0.05); The arterial stiffness and ABI level of patients with COPD in the observation group were higher than those of healthy subjects in the control group (P < 0.05), indicating that the continuous development of COPD will lead to increased arterial stiffness and abnormal ultrasound examination.…”
Section: Discussionmentioning
confidence: 99%
“…A commonly used indicator of the severity and progression of the disease in COPD is expiratory volume per second (FEV1). However, it is weakly associated with symptoms and administration difficulties in elderly patients [6][7] . Therefore, there is a need for other markers that are better and easy to apply to sick and elderly patients.…”
Section: Introductionmentioning
confidence: 99%